analisa keselamatan dan kesehatan kerja pada pengoperasian forklift di Pt. equiport inti indonesia - Harjum La Bau; Muh Fadhil Safli; Sudarsono; La Ode Ahmad Barata (Program Pendidikan Vokasi Teknik Mesin, 2022)
Occupational Health and Safety (K3) is our effort to create a healthy and safe work environment so as to reduce the probability of occupational accidents and diseases due to negligence which results in demotivation and deficiency in work productivity. At PT. Equiport Inti Indonesia, the application of forklift operating safety regulations has not been carried out thoroughly. The non-implementation of the implementation of the regulations as a whole can trigger work accidents. The purpose of this final project is to find out the steps taken by the company in preventing work accidents in forklift operations. The method used in this final project uses interviews and direct observation in the company to fill in the checklist table that has been prepared as a data collection tool. The analysis in this final project uses a fishbone diagram. The use of fishbone diagrams is carried out to trace the causes and effects that arise from the deficiencies found that can lead to forklift work accidents. The results of this final project show that PT. Equiport Inti Indonesia still lacks in implementing safety standards in forklift operations, including the absence of pedestrian paths, incomplete forklift safety signs, and the operator's lack of seriousness in operating forklifts. From the results of this final project, it can be concluded that the company pays little attention to the procedures for implementing occupational safety and health in forklift operations.